Criteria equation for optimizing operating modes of a filter centrifuge - Shayakhmetova, Мадина; Kasenov, Амиржан; Aigerim, Айгерим; Lobasenko, Борис (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
In the Republic of Kazakhstan, one of the priority areas for the development of medium and small enterprises is the introduction of waste-free processing of raw materials. These industries include medium and small meat processing enterprises. In improving the waste-free technology of meat products, the production of dry feed is in high demand due to the high nutritional value of the latter, which often surpasses other feed products. In the production of dry animal feed, the centrifugation process is used to separate the fat from the flakes. The use of the centrifugation process in the separation of fat from the pulp leads to the fact that the quality of the fat released is significantly higher than in the pressing and extraction processes. Taking into account the needs of the development of meat processing production, it is of great importance to improve the separation process of liquid heterogeneous systems on centrifugal equipment, which provides for a reduction in the specific energy consumption of equipment and its own opportunities to increase production volumes.